2010
DOI: 10.1111/j.1443-1661.2010.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Endoscopic Submucosal Dissection of Large Colorectal Tumors

Abstract: Based on our analysis of the learning curve, approximately 80 procedures must be carried out to acquire skill with ESD for large colorectal tumors. However, approximately 40 procedures were sufficient to acquire skill in avoiding perforations during the ESD procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
3
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 34 publications
2
127
3
5
Order By: Relevance
“…Therefore, the clinical outcomes such as proficiency and procedure time in our study might be greater than those of previous reports. 19,22 As colorectal epithelial tumors in our study were relatively smaller than those of previous reports, they would also affect the clinical outcomes. 19 The third limitation is that the study was designed for just one endoscopist in a single center.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Therefore, the clinical outcomes such as proficiency and procedure time in our study might be greater than those of previous reports. 19,22 As colorectal epithelial tumors in our study were relatively smaller than those of previous reports, they would also affect the clinical outcomes. 19 The third limitation is that the study was designed for just one endoscopist in a single center.…”
Section: Discussioncontrasting
confidence: 42%
“…19,22 As colorectal epithelial tumors in our study were relatively smaller than those of previous reports, they would also affect the clinical outcomes. 19 The third limitation is that the study was designed for just one endoscopist in a single center. However, it is not easy to conduct a multicenter study with multiple endoscopists because there might be heterogeneity in basic skill and ability to acquire the procedure among endoscopists from different institutes.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…На начальном этапе внедре-ния в практику указанный метод сопровождался тех-ническими трудностями и большим количеством осложнений, что постепенно удалось во многом пре-одолеть с накоплением опыта и отработкой методики данного вмешательства [16,17]. Как показал ретро-спективный анализ [18], частота осложнений ESD уменьшается в среднем после 40 выполненных опера-ций. Подслизистая диссекция в толстой кишке харак-теризуется повышенным риском перфорации стенки органа, так как эта стенка здесь тоньше, а стабилиза-ция эндоскопа технически более сложна, чем в желуд-ке или пищеводе [17].…”
Section: Introductionunclassified
“…Dinis-Ribeiro et al [52] suggested that only after performing 20-40 ESDs in the distal stomach, should lesions located in proximal sites in the stomach, esophagus, and colon be tried. Hotta et al [53] reported on the learning curve for colonic ESD, and they concluded that performance of approximately 40 procedures was sufficient to acquire the skill to avoid causing perforations during the ESD procedure, and approximately 80 procedures must be carried out to acquire adequate skill to successfully remove large colorectal tumors. Sakamoto et al [54] reported that trainees can perform colorectal ESD safely and independently after preparatory training and experience with more than 30 cases.…”
Section: Learning Curve For Gastric Esdmentioning
confidence: 99%